Influência da densidade de carga e da massa molar da poliacrilamida na reologia de sistemas microemulsionados - Barros, Rosemiro Marinho (2014)
The knowledge of the rheological behavior of microemulsionated systems (SME) is of fundamental importance due to the diversity of industrial applications of these systems. This dissertation presents the rheological behavior of the microemulsionated system formed by RNX 95/alcohol isopropyl/p-toulen sodium sulfonate/kerosene/distilled water with the addition of polyacrylamide polymer. It was chosen three polymers of the polyacrylamide type, which differ in molar weight and charge density. It was studied the addition of these polymers in relatively small concentration 0,1% in mass and maximum concentration of 2,0%. It was made analysis of flow to determine the appearing viscosities of the SME and rheological parameters applying Bingham, Ostwald de Waale and Herschell-Buckley models. The behavior into saline environment of this system was studied for a solution of KCl 2,0%, replacing the distilled water. It was determined the behavior of microemulsions in relation with the temperature through curves of flow in temperatures of 25 to 60ºC in variations of 5ºC. After the analysis of the results the microemulsion without the addition of polymer presented a slight increase in its viscosity, but it does not mischaracterize it as a Newtonian fluid. However the additive systems when analyzed with low concentration of polymer adjusted well to the applied models, with a very close behavior of microemulsion. The higher concentration of the polymer gave the systems a behavior of plastic fluid. The results of the temperature variation point to an increase of viscosity in the systems that can be related to structural changes in the micelles formed in the own microemulsion without the addition of polymer